Therapeutic approach with virtual reality in the phobia of flying: a case study - Valdés-Díaz, María; Guillot-Valdés, María (Anales de Psicología / Annals of Psychology, 2025)
Flight phobia is an anxiety disorder whose main symptoms are intense and irrational fears, exposure to which causes high levels of anxiety and consequent avoidance of flying. Virtual reality (VR) has been shown to be effective in the treatment of specific phobias, as patients can confront their fears in a controlled and repetitive manner in a virtual environment, allowing them to learn coping strategies and reduce associated discomfort. The aim of this study is to reduce the anxiety, worry and fear associated with flying through the use of virtual reality. The following is a case study of a 23-year-old woman with a phobia of flying since adolescence. Anxiety occurs during the flight and rarely in the days before. ABA design (pre-treatment-post-test). A semi-structured interview and the STAI, PSQW, EMV and EPAV questionnaires were used to establish baseline, with high scores for trait and state anxiety, worry and fear of flying. An intervention of 8 one-hour sessions was planned, with gradual exposure to virtual reality prior to live exposure. The patient showed a clinically meaningful reduction in her negative emotions associated with flying and was able to fly. VR may be an effective tool in clinical practice for graded exposure in the treatment of fear of flying.